Dynamic changes and future trend predictions of the global burden of anxiety disorders: analysis of 204 countries and regions from 1990 to 2021 and the impact of the COVID-19 pandemicResearch in context - Si Chen; Wei Huang; Min Zhang; Yan Song; Chunshan Zhao; Hongwei Sun; Yanyu Wang; Jihong Wang; Yali Sun; Lei Zhou; Yan Zhu; HongYuan Wang; et al. (EClinicalMedicine)
Summary: Background: Anxiety disorders is a significant contributor to the Global Burden of Diseases (GBD), particularly in the aftermath of the COVID-19 pandemic, which has exacerbated the issue. Previous studies have not examined the impact of the COVID-19 pandemic on anxiety disorders over the entire time series, nor have they offered predictions regarding future trends of global anxiety disorders in the aftermath of the pandemic. This study aims to present the Age-Standardized Prevalence Rates (ASPR), Age-Standardized Incidence Rates (ASIR), and disability-adjusted life years (DALYs) associated with anxiety disorders from 1990 to 2021 across 204 countries and regions, emphasizing the age structure and the disease burden following the pandemic. Additionally, it examines the relationship between the burden of anxiety disorders and the COVID-19 pandemic, as well as trend predictions for the incidence of anxiety disorders from 2022 to 2050. Methods: We analysed data from the GBD 2021 study, employed the GBD method to integrate epidemiological data on ASPR, ASIR, and DALYs to accurately assess the global burden of anxiety disorders across various regions, genders, and age groups. Additionally, joint point regression analysis was applied to rigorously examine the time trends of anxiety disorders from 1990 to 2021, calculating the annual percentage change (APC), annual average percentage change (AAPC), and their corresponding 95% confidence intervals (CIs). Furthermore, path analysis was utilized to investigate the impact pathways between the COVID-19 pandemic and anxiety disorders. Finally, a Bayesian age-period-cohort (BAPC) model was employed to predict the prevalence trends of anxiety disorders from 2022 to 2050. Findings: From 1990 to 2021, the ASPR, ASIR, and DALYs associated with anxiety disorders worldwide exhibited a significant upward trend, particularly evident from 2019 to 2021, during which all three metrics experienced a sharp increase. The most pronounced changes in the burden of anxiety disorders from 2019 to 2021 were observed in high socio-demographic index (SDI) regions, where the ASIR surpassed expected levels in tropical Latin America, high-income North America, and Australia in 2021. Bulgaria recorded the highest increase in anxiety disorders burden during this period, with a change rate of 0.32, while Bhutan experienced the smallest increase, with a total change rate of 0.02. Notably, the global anxiety disorders burden among women is greater than that among men. From 2019 to 2021, women aged 20–24 years were particularly impacted by the COVID-19 pandemic, with a change rate of 0.21. Additionally, the ASIR of COVID-19 pandemic in 2021 had a significant positive correlation with the prevalence of anxiety disorders, standardized path coefficient value of 0.224 (z = 2.708, P < 0.01). Projections indicate that by 2050, the number of individuals affected by anxiety disorders may reach 87.36 million (95% UI: 59.28–115.44). It is also anticipated that the prevalence of anxiety disorders among the 15–19 age group will exceed that of other age groups by 2050. Interpretation: The COVID-19 pandemic has significantly impacted the future burden of anxiety disorders, necessitating greater attention towards young individuals, particularly women. There is an urgent need for the adoption of targeted prevention and treatment strategies on a global scale, especially in high SDI regions, to effectively address the escalating issue of anxiety disorder burden. Funding: Jilin Province 2023 Health Science and Technology Capability Enhancement Plan Project (2023LC024) and Jilin Provincial Department of Science and Technology project (20230203054SF). Research Project on Teaching Reform of Graduate Education at Beihua University (JG [2024]009), Education and Teaching Reform Project of Beihua University (21xjyb-1241759), Jilin Province Education Science “14th Five Year Plan” Project (GH24295).